Government Propaganda at the Peace Action on September 1, 2025 in Lampung: Between Image Management and Discourse Control - Aisyah Putri Anggun Damaiyanti (Sean Institute, 2026)
This study analyzes the form and strategy of government propaganda in constructing the narrative of the 'most peaceful demonstration in Indonesia' during the September 1, 2025 protest in Lampung. Using Agenda Setting and Uses and Gratification theories, this study reveals how the government and media shaped a dominant 'peaceful' narrative that diverted public attention from the demonstrators’ substantive demands. The findings indicate that the propaganda operated on two levels: agenda-setting through media framing and audience gratification through emotional and social engagement on social media. This dual dynamic shows that digital propaganda is not only a top-down process but also involves active public participation that reinforces government narratives.